Love is Part of What We Need. (November 2022) - Mazelis, Joan Maya; Finkle, Harvey
It's been over two and a half years since we all first talked about "social" distancing. Though physical distancing was crucial as we began to battle COVID-19, the term social distancing was a misnomer. We need our connections to other people. This need for emotional connection and support is universal, but sometimes people forget that those in poverty have emotional needs in addition to financial ones. A sociologist and a photographer who have decades of experience spending time with people living in poverty and documenting their lives observe the beauty and power of emotional connections between people who are struggling.